Life satisfaction of Palestinian and Polish students after pandemic COVID-19 - Krzysztof Zdziarski; Anna Knyszyńska; Katarzyna Karakiewicz-Krawczyk; Mariam Awad; Salam Awad; Narmeen Qumsieh; Marek Landowski; Beata Karakiewicz (Frontiers in Public Health)
The COVID-19 pandemic has had a huge impact on the lives of all social groups around the world, including students who have had to face remote learning and isolation. Regardless of cultural, linguistic and religious differences, every young person is looking for the meaning of life and their place in the world. This process includes physical, mental, social and spiritual aspects. The pandemic has highlighted the importance of these elements anew, especially in the face of threats to health and life. The study included two groups of students: 238 from Palestine and 293 from Poland. The question was asked: what factors have the greatest impact on students’ sense of happiness after the COVID-19 pandemic? The results showed interesting differences in their approach to life and happiness. Palestinian students perceive life more optimistically and attach importance to family ties, physical health and religion. Polish students attach importance to social activity, meetings with friends, traveling, listening to music and watching movies. For them, these forms of spending free time are important in the context of mental regeneration and escape from stress. They emphasize that a good financial situation gives them a sense of security and allows them to pursue their passions and interests. Both groups do not associate happiness with psychoactive substances. The results indicate a generally positive assessment of students’ life satisfaction after the pandemic. Research shows that there are universal values that give a sense of happiness and life satisfaction to young people around the world.